1987
DOI: 10.1152/jappl.1987.63.5.1966
|View full text |Cite
|
Sign up to set email alerts
|

Effect of hyperoxia on glutathione levels and glutamic acid uptake in endothelial cells

Abstract: Intracellular glutathione was increased by 80% after exposure of bovine pulmonary arterial endothelial cells to 80% O2 (hyperoxia) for 24 h. No change in glutathione occurred in cells exposed to hypoxia (3% O2) for a corresponding period of time. The rate of uptake of [3H]glutamic acid also increased by 35-55% after 24 h of exposure of cells to hyperoxia, whereas exposure to hypoxia had no effect on the [3H]glutamic acid uptake. The increase in glutamic acid uptake reflected a specific effect on amino acid tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

1993
1993
2005
2005

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The importance of GSH in normal functioning of cellular defense mechanisms is well recognized, and depletion of GSlI by fasting, restricting dietary sources of divalent sulfur or treatment with L-buthionine-[S.R]-sulfoximine has been reported to enhance the sensitivity of experimental animals to the adverse effects of hyperoxia (17)(18)(19)(20) and other potentially damaging challenges such as has been characterized for toxic doses of acetaminophen (31). In addition to the stresses created by increased oxidation of GSH to GSSG.…”
Section: Methodsmentioning
confidence: 99%
“…The importance of GSH in normal functioning of cellular defense mechanisms is well recognized, and depletion of GSlI by fasting, restricting dietary sources of divalent sulfur or treatment with L-buthionine-[S.R]-sulfoximine has been reported to enhance the sensitivity of experimental animals to the adverse effects of hyperoxia (17)(18)(19)(20) and other potentially damaging challenges such as has been characterized for toxic doses of acetaminophen (31). In addition to the stresses created by increased oxidation of GSH to GSSG.…”
Section: Methodsmentioning
confidence: 99%
“…Oxidants (hyperoxia and H 2 O 2 ), and agents such as sodium arsenite, cadmium, electrophilic compounds and diethyl maleate, also induce cystine transport in various lung cells, macrophages and erythrocytes that is analogous to the X c --transport system, a sodium-independent inducible system specific to the intracellular transport of cystine and glutamate [130±133]. It has been shown that exposure of rats to hyperoxia results in increases in total lung GSH within 24 h [6,134]. It is, therefore, possible that induction of cystine or cysteine transport could contribute to the increased GSH levels in lungs after exposure to hyperoxia [6,134].…”
Section: Role Of C-glutamyl Transpeptidase In the Regulation Of Glutamentioning
confidence: 99%
“…It has been shown that exposure of rats to hyperoxia results in increases in total lung GSH within 24 h [6,134]. It is, therefore, possible that induction of cystine or cysteine transport could contribute to the increased GSH levels in lungs after exposure to hyperoxia [6,134].…”
Section: Role Of C-glutamyl Transpeptidase In the Regulation Of Glutamentioning
confidence: 99%
“…In the liver, both transport systems have been found, but only the sodium-independent system was inducible [37]. In bovine pulmonary artery endothelial cells (BPAEC), the x c -system was found to be sodium-independent and inducible by diethyl maleate (DEM), arsenite and 1,3-bis(2-chloroethyl)-1-nitrosurea (BCNU) [23,24,39,40]. In human fibroblasts is rather complex, and our knowledge of it is far from complete, especially with regard to the type II pneumocytes.…”
Section: Glutathione In Perspectivementioning
confidence: 99%
“…The activity of transsulphuration differs in isolated liver cells from the in vivo situation, in that isolated liver cells (like other cell types in vitro) usually lack the transsulphuration pathway, and thus require exogenous cysteine or cystine [22]. Cysteine is one of the three components of GSH, and the ratelimiting substrate for GSH synthesis in various cell types in culture, especially under conditions of oxidative stress [22][23][24]. Glutamate or glycine are rarely rate-limiting [22,25].…”
Section: Amino Acid Transport Systems and Gsh Synthesis (Fig 3)mentioning
confidence: 99%